Meat quality of broiler breast fillets with white striping and woody breast muscle myopathies - Tijare, V. V.; Yang, F. L.; Kuttappan, V. A.; Alvarado, C. Z.; Coon, C. N.; Owens, C. M. (Poultry science, 2016)
The global poultry industry has been faced with emerging broiler breast meat quality issues including conditions known as white striping (WS, white striations parallel to muscle fibers) and woody breast (WB, hardness of raw fillet). Experiments were conducted to evaluate effects of WS and WB hardness on meat quality traits in broiler breast fillets. In Exp. 1, birds were processed at approximately 9 wk of age and deboned at 4 h postmortem (PM); in Exp. 2, birds were processed at approximately 6 and 9 wk of age and deboned at 2 h PM. Fillets were categorized as: normal for both white striping and woody breast (NORM); moderate for white striping and mild for woody breast (MILD); severe for white striping and mild for woody breast (WS); severe for woody breast and moderate for white striping (WB); or severe for both white striping and woody breast (BOTH). Sarcomere length, gravimetric fragmentation index, marination uptake, cook loss, and Meullenet-Owens razor shear energy (MORSE) values on non-marinated and marinated fillets were assessed. Sarcomeres tended to be longer (P = 0.07) with increasing severity of WS and WB in both experiments and gravimetric fragmentation index did not differ (P > 0.05) among categories. Marinade uptake decreased (P < 0.05) with increasing severity of WS and WB. Cook losses of non-marinated and marinated fillets were greatest (P < 0.05) in the BOTH category. Even though MORSE values did not differ (P > 0.05) in non-marinated fillets, the marinated BOTH fillets had greater MORSE values (P < 0.05) than other categories of fillets in Exp. 1. Non-marinated NORM fillets had greater (P < 0.05) MORSE values than the other categories at 6 wk age; however, MORSE values did not differ (P > 0.05) among categories of marinated breasts. At 9 wk, WS and BOTH were higher (P < 0.05) in MORSE compared to NORM for non-marinated fillets, but similar to NORM marinated fillets. Results suggest that severe degrees of white striping and woody breast, individually or in combination, negatively impact meat quality, especially water holding capacity attributes such as marinade uptake and cook loss.